Options and limits of angle stable plates in the treatment of comminuted radial head fractures - Raven, Tim Friedrich; Doll, Julian; Westhauser, Fabian; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (Journal of orthopaedics, 2018)
Objective - New angle-stable plates provide more stability and better anatomical fit than previous plates. - Methods - 22 patients treated with an angle-stable plate were included. Postoperative the outcomes were evaluated according to the scoring systems of Morrey, Radin and Riseborough. - Results - 3 patients received a score of excellent, 14 good, and 5 satisfactory. We detected 3 cases of implant failure and 2 cases of postoperative neurological damage. 3 patientes received a radial head necrosis. - Conclusions - Our results show that the angle-stable radial head locking plate can only be used in limited cases in the treatment of multi-fragment radial head fractures.
Gesehen am 27.05.2019